Analysis of platelet indice (MPV, PDW) on the severity of COVID-19 patients - Halimi, Sofwan; Setyaningrum, Endah; Sutyarso, Sutyarso; Nurcahyani, Nuning; Hidayat, Hidayat (Biogenesis: Jurnal Ilmiah Biologi, 2023)
The COVID-19 virus infection some time ago caused a pandemic and became a health problem in the world, including Indonesia. The cause of COVID-19 infection is the SARS-CoV-2 virus which can be detected by Real Time reverse-transcriptase polymerase chain reaction (rRT-PCR). Platelets play a role in inflammation and the pathogenesis of various inflammatory clinical conditions which are also affected by COVID-19 infection, which can change according to the severity of the infection. The purpose of this study was to analyze differences in MPV and PDW in the severity of COVID-19 patients. This type of research is an analytic observational study with a cross sectional research design. Data on platelet index values and the degree of severity were obtained from medical records during the period June to August 2021 from 209 COVID-19 patients treated at RSUD Dr. H. Abdul Moeloek Lampung Province. Statistical tests were carried out using the Kruskal Wallis Annova test, followed by the Mann Whitney test. The results showed that there was a significant difference in the PDW index (p = 0.004) to the degree of severity of COVID-19, while the MPV index was not significantly different to the degree of severity of COVID-19. Excessive production of cytokines and acute phase reactants due to immune response and inflammation for COVID-19 infection, thereby affecting the development of megakaryocytes resulting in changes in the PDW Platelet index, the pathogenesis of SARS-CoV-2 infection is very complex and it is possible that the early stages of the disease do not affect all parameters hematology.